Cosmopsychism in the bhagavad gita: Exploring consciousness in the cosmos - K M, Anjuna (Dharmakirti : International Journal of Religion, Mind and Science, 2024)
Background: Vedic knowledge, drawn from ancient texts like the Vedas and the Bhagavad Gita, offers a deep understanding of consciousness and its place in the universe. Methods: These scriptures emphasize that consciousness isn't just a result of brain functions but a fundamental element of existence throughout the cosmos. Findings: The Bhagavad Gita, widely acclaimed as a philosophical and spiritual masterpiece, offers deep wisdom on consciousness and the universe. A fascinating concept explored in the Gita is cosmopsychism—the idea that the cosmos possesses consciousness. Conclusion: This article explores cosmopsychism as depicted in the Bhagavad Gita, analyzing its themes and teachings that suggest a universe filled with consciousness.